The intervention of organizational sustainability in the effect of organizational culture on open innovation performance: A case of thai and chinese SMEs - W. A. Srisathan; C. Ketkaew; P. Naruetharadhol (Cogent Business & Management, 2020)
Small- and medium-sized enterprises (SMEs) are largely encouraged to take an open innovation model as a systematic area for R&D to expand networks in science and technology operation (Sci-Tech), especially in Thailand and China. Our paper examines the relationship between organizational culture (OC) and open innovation performance (OIP) of SMEs and the mediating effect of organizational sustainability (OS). Our investigation of 300 SMEs from different business industries in Thailand and China reveals that organizational sustainability significantly intervenes in the interaction of organizational culture and open innovation performance. From the findings, it is established that organizations should set robust and appropriate strategies for organizational sustainability to have excellent innovation outputs in SMEs' performance. This paper also shows the significant effect of organizational culture on organizational sustainability in that cultural characteristics maintain the core business competencies in terms of marketing, operations, customer orientation, capital management, and monitoring & evaluation for sustainability. Such elements of organizational sustainability operate in a significant mediator contribution to SMEs' performance to manage open innovation. As a practical contribution, this paper suggests managers realize the crucial elements of organizational culture, such as leadership, teamwork, and organizational climate, to improve performance by combining organizational sustainability in their strategic decisions made during the open innovation processes.
Keywords: 650